2012
DOI: 10.1093/icc/dts018
|View full text |Cite
|
Sign up to set email alerts
|

Inter-firm rivalry and firm growth: is there any evidence of direct competition between firms?

Abstract: Inter-firm competition has received much attention in the theoretical literature, but recent empirical work suggests that the growth rates of rival firms are uncorrelated, and that firm growth can be taken as an essentially independent process. We begin by investigating the correlations of the growth rates of competing firms (i.e. the largest and second-largest firms in the same industry) and observe that, surprisingly, the growth of these firms can be taken as independent. Nevertheless, peer-effect regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Previous studies have shown diverse conclusions on the relationship between leadership and firm performance. However, these studies did not consider firm size to be a factor and included both small and large firms [38][39][40]. For large firms only, Boone and colleagues (2007) observed that the forces of competition were more significant, and the performance relationship between competing firms was easier to observe [41].…”
Section: Relationship Of Market Leadership and Profitmentioning
confidence: 99%
“…Previous studies have shown diverse conclusions on the relationship between leadership and firm performance. However, these studies did not consider firm size to be a factor and included both small and large firms [38][39][40]. For large firms only, Boone and colleagues (2007) observed that the forces of competition were more significant, and the performance relationship between competing firms was easier to observe [41].…”
Section: Relationship Of Market Leadership and Profitmentioning
confidence: 99%
“…Farmers in densely clustered markets can face intense competition (Folta, Cooper, and Baik 2006;Crozet, Mayer, and Mucchielli 2004), which may create a difficult operating environment (Stucke 2013;Coad and Teruel 2013). Such circumstances are likely to be why the density of farmer concentration can reduce farmers' profitability and, ultimately, raise poverty rates.…”
Section: Introductionmentioning
confidence: 99%
“…When simulating industrial dynamics it is common to let firms acquire output market shares when they are capable of undercutting the prices of their competitors; that is, when they have higher physical efficiency. Sutton (2007) explores these dynamics and finds that changes in firms' output market shares are independent of each other in most industries while Coad and Teruel (2013) explore the question with a clever econometric technique and show that, when endogeneity is sufficiently accounted for, the negative expected correlation among changes in firms' output market shares can indeed be identified. A theory of selection based on output market shares suggests that the size measure in decomposition analysis is sales or production.…”
Section: Measuring Selectionmentioning
confidence: 99%
“…Coad and Teruel (2013); Bottazzi et al (2010); Coad (2007)) have argued that firms' management may pursue other strategies than growth even when the firm has relatively high productivity, and thus that the effect of productivity on growth depends on a general parameter representing, for example, the propensity to re-invest profits.…”
Section: Introductionmentioning
confidence: 99%